Attention levels in young children who stutter. Issue 4 (2nd October 2019) - Costelloe, Sarah; Davis, Steve; Cavenagh, Penny; Doneva, Silviya P.
Abstract: The purpose of this study was to determine whether children who stutter (CWS) and children who do not stutter (CWNS) differ in terms of attentional ability. Participants were 40 age- and gender-matched CWS and CWNS (aged between 72 and 120 months). Attentional ability was assessed using the Test of Everyday Attention for Children (TEA-Ch), a clinical assessment battery comprising 13 attentional measures, assessing three areas of attention: selective attention, sustained attention, and attentional switching. A low score on the assessment indicates attentional difficulty. There was an overall tendency for CWS to score lower than CWNS on all 13 TEA-Ch measures and all three attentional abilities. This difference reached statistical significance for the sustained attentional component. The present study provides support for the hypothesis that there are some differences between CWS and CWNS in terms of attentional ability. The findings are interpreted within existing models of attention with regard to previous studies of attention in CWS.